The use of multimedia in English language teaching to support English teaching practice - Bob Rachman; Intan Pradita (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2019)
This study was implemented in private Islamic secondary school in Yogyakarta. This study aims to support student motivation in studying English with multimedia as the assistance. The use of multimedia such as pictures, videos, and games are expected to create an active atmosphere of learning and teaching. This practice was conducted for four times and the result show that students were very engage while studying English and the class atmosphere become more fun and less monotone. How is the use of multimedia mediates activity to teach formal invitation in a private Islamic Secondary School? I learned that students demonstrated better learning engagement during the lesson. In addition, it also encourage the students to be more creative and active. Keywords: Multimedia: Learning Media: Teaching English